Technology Enhanced Learning and Personality Development: A Case of Secondary School Students - Mahnaz, Wajid; Akram, Huma (ACADEMIA International Journal for Social Sciences, 2026)
The increasing integration of social media, and online learning platforms have significantly reshaped students’ behavioral and emotional development. Given that we aimed to examine technology use among secondary school students and its impact on their personality. The study adopted a quantitative correlational research design under the positivist paradigm to analyze the relationship between variables. The population of the study consisted of approximately 310 secondary schools and 52,000 students of District Rawalpindi. A sample of 400 secondary school students was selected through proportionate stratified random sampling technique to ensure representation of government and private schools. A structured questionnaire based on a five-point Likert scale was used as the research tool, comprising items related to technology use and Big Five personality traits. Data was analyzed using SPSS through descriptive statistics, correlation, and regression analysis. The first observation identified that the level of technology use among secondary school students was moderate, indicating balanced but frequent digital engagement, and it was recommended that schools and parents should guide students toward responsible and educational use of technology. The significance of the study lay in its contribution to understanding the psychological and behavioral effects of technology use on adolescents, providing valuable insights for educators, parents, and policymakers to develop strategies for promoting healthy personality development in a digital environment.